If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3(2x + -3) = 0.7(8 + -1x) Reorder the terms: 0.3(-3 + 2x) = 0.7(8 + -1x) (-3 * 0.3 + 2x * 0.3) = 0.7(8 + -1x) (-0.9 + 0.6x) = 0.7(8 + -1x) -0.9 + 0.6x = (8 * 0.7 + -1x * 0.7) -0.9 + 0.6x = (5.6 + -0.7x) Solving -0.9 + 0.6x = 5.6 + -0.7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.7x' to each side of the equation. -0.9 + 0.6x + 0.7x = 5.6 + -0.7x + 0.7x Combine like terms: 0.6x + 0.7x = 1.3x -0.9 + 1.3x = 5.6 + -0.7x + 0.7x Combine like terms: -0.7x + 0.7x = 0.0 -0.9 + 1.3x = 5.6 + 0.0 -0.9 + 1.3x = 5.6 Add '0.9' to each side of the equation. -0.9 + 0.9 + 1.3x = 5.6 + 0.9 Combine like terms: -0.9 + 0.9 = 0.0 0.0 + 1.3x = 5.6 + 0.9 1.3x = 5.6 + 0.9 Combine like terms: 5.6 + 0.9 = 6.5 1.3x = 6.5 Divide each side by '1.3'. x = 5 Simplifying x = 5
| 5c+7=95-6c | | 5x-69=7x+21 | | 1/2x-9=x-3 | | .25x-y=3 | | 2x+10=5x-80 | | 12x-25=8x+23 | | -5x/2=-1 | | 4x-5y=-32 | | 10x+20x=150 | | 4x-5y=-32graph | | 3x/2=-3 | | 8x+5-4x=-20 | | x-1=x^2-6x+9 | | -1x/3=-12 | | 4t+16-6= | | x/5+7=27 | | 5x^2-40x-10=0 | | 1x/3=0 | | 5x^2+40x-10=0 | | f=200+25+.02x | | x^2-20x-76=-7 | | 6x-5x+3/4=-1/12 | | 10x-24=2x-56 | | 14x+8/2=39 | | x^2+10x-14=10 | | a/12=8 | | x^2-6x-17=10 | | 4=-2/-5 | | 1x^2+3x-24=0 | | 0.3(x+50)+0.7x=40 | | 11=-3x/-4 | | 9x^2+18x-23=4 |